2021
DOI: 10.1177/1758835920949418
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck cancer: the role of anti-EGFR agents in the era of immunotherapy

Abstract: Head and neck cancers (HNC) represent the seventh most frequent cancer worldwide, with squamous cell carcinomas as the most frequent histologic subtype. Standard treatment for early stage diseases is represented by single modality surgery or radiotherapy, whereas in the locally advanced and recurrent or metastatic settings a more aggressive multi-modal approach is needed with locoregional intervention and/or systemic therapies. Epidermal Growth Factor Receptor (EGFR) plays an important role in HNC biology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 115 publications
(176 reference statements)
0
38
0
Order By: Relevance
“…It is worth noting that both molecules are therapeutic targets. In this regard, it is relevant that cetuximab was the first targeted therapy approved for the treatment of HNSCC [ 63 ] and is currently the only clinically approved targeted therapy for this malignancy, although its use is limited [ 64 ]. Su et al suggested that the benefit of EGFR inhibitors is probably restricted to p16+ cases and depends on the type of treatment [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that both molecules are therapeutic targets. In this regard, it is relevant that cetuximab was the first targeted therapy approved for the treatment of HNSCC [ 63 ] and is currently the only clinically approved targeted therapy for this malignancy, although its use is limited [ 64 ]. Su et al suggested that the benefit of EGFR inhibitors is probably restricted to p16+ cases and depends on the type of treatment [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Su et al suggested that the benefit of EGFR inhibitors is probably restricted to p16+ cases and depends on the type of treatment [ 65 ]. Various clinical studies are currently being carried out in HNSCC with several EGFR inhibitors, especially in locally advanced disease, some in the context of HPV, as well as recurrence and metastasis [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Frequent abnormalities in the expression of EGFR and EGFR-mediated activation of downstream signaling pathways have been detected in many human malignancies. Anti-EGFR targeted therapy has been brought into focus in recent years ( Chen et al, 2020a ; Fasano et al, 2021 ). To date, two primary species of EGFR targeted agents include monoclonal antibodies (McAb) and small molecule tyrosine kinase inhibitors (TKI).…”
Section: Introductionmentioning
confidence: 99%
“…EGFR mAb EGFR (epithelial growth factor receptor) is a member of the ErbB/HER family, overexpressed in about 90% of HNSCCs. Its expression is related to poor survival because of resistance to radiotherapy and local treatments; nevertheless, its prognostic role is still quite controversial [5]. In 2006, cetuximab, an anti-EGFR monoclonal antibody (mAb), was approved in HNSCC treatment.…”
Section: Introductionmentioning
confidence: 99%